The Neuroimmune Interface and Chronic Pain Through the Lens of Production Animals - Johnston, Charlotte H.; Whittaker, Alexandra L.; Franklin, Samantha H.; Hutchinson, Mark R. (Frontiers in Neuroscience, 2022)
Communication between the central nervous system (CNS) and the immune system has gained much attention for its fundamental role in the development of chronic and pathological pain in humans and rodent models. Following peripheral nerve injury, neuroimmune signalling within the CNS plays an important role in the pathophysiological changes in pain sensitivity that lead to chronic pain. In production animals, routine husbandry procedures such as tail docking and castration, often involve some degree of inflammation and peripheral nerve injury and consequently may lead to chronic pain. Our understanding of chronic pain in animals is limited by the difficulty in measuring this pathological pain state. In light of this, we have reviewed the current understanding of chronic pain in production animals. We discuss our ability to measure pain and the implications this has on animal welfare and production outcomes. Further research into the neuroimmune interface in production animals will improve our fundamental understanding of chronic pain and better inform human clinical pain management and animal husbandry practices and interventions.